THE FOUR PILLARS OF EDUCATION BY UNESCO AND THE METAVERSE: REPOSITIONING ISLAMIC EDUCATION - Hasan, Khairuddin (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2023)
The research aims to reveal the position of Islamic education towards development in the form of UNESCO's four pillars of education offering and the use of the metaverse. This research uses literature study as a qualitative method and approach. Primary sources and secondary sources that are relevant to the research variables are traced first to obtain the required data. Data is classified to facilitate analysis and drawing conclusions. The four pillars namely learning to know, learning to do, learning to be and learning to live together have principles that are aligned and Islamic education can use them in the learning process. The Metaverse, which offers a more complex life in the virtual realm, offers many benefits as well as several risks. Metaverse eases the learning process and reduces time and space constraints. Metaverse also helps provide a more comprehensive understanding of learning materials. However, there are issues of morality that have the potential to be violated in virtual space. In fact, the virtual realm is not a value-free realm and is still bound by the values ​​espoused by civilized society. Islamic education has a role to strengthen the application of these values ​​so that people do not fall into immoral acts even though they are carried out in the virtual realm as the second realm of life in this era. It is necessary to strengthen the morality of society so that there is no dichotomy in the living space which can lead to actions that demean human dignity and violate the rights of other individuals.